Induction of dsRNA-activated protein kinase links mitochondrial unfolded protein response to the pathogenesis of intestinal inflammation. Issue 9 (13th October 2011) - Rath, Eva; Berger, Emanuel; Messlik, Anja; Nunes, Tiago; Liu, Bo; Kim, Sandy C; Hoogenraad, Nick; Sans, Miquel; Sartor, R Balfour; Haller, Dirk
Abstract : Objective: Inflammatory bowel diseases (IBDs) feature multiple cellular stress responses, including endoplasmic reticulum (ER) unfolded protein responses (UPRs). UPRs represent autoregulatory pathways that adjust organelle capacity to cellular demand. A similar mechanism, mitochondrial UPR (mtUPR), has been described for mitochondria. ER UPR in intestinal epithelial cells (IECs) contributes to the development of intestinal inflammation, and since mitochondrial alterations and dysfunction are implicated in the pathogenesis of IBDs, the authors characterised mtUPR in the context of intestinal inflammation. Methods: Truncated ornithine transcarbamylase was used to selectively induce mtUPR in a murine IEC line. Dextran sodium sulphate (DSS) was administered to PKR (double-stranded- R NA-activated p rotein k inase) knockout mice to induce IEC stress in vivo and to test for their susceptibility to DSS-induced colitis. Expression levels of the mitochondrial chaperone chaperonin 60 (CPN60) and PKR were quantified in IECs from patients with IBDs and from murine models of colitis using immunohistochemistry and Western blot analysis. Results: Selective mtUPR induction by truncated ornithine transcarbamylase transfection triggered the phosphorylation of eukaryotic translation initiation factor (eIF) 2α and cJun through the recruitment of PKR. Using pharmacological inhibitors and small inhibitory RNA, the authors identified mtUPR-induced eIF2α phosphorylation and transcription factor activation (cJun/AP1) as being dependent on the activities of the mitochondrial protease ClpP and the cytoplasmic kinase PKR. Pkr −/− mice failed to induce CPN60 in IECs upon DSS treatment at early time points and subsequently showed an almost complete resistance to DSS-induced colitis. Under inflammatory conditions, primary IECs from patients with IBDs and two murine models of colitis exhibited a strong induction of the mtUPR marker protein CPN60 associated with enhanced expression of PKR. Conclusion: PKR integrates mtUPR into the disease-relevant ER UPR via eIF2α phosphorylation and AP1 activation. Induction of mtUPR and PKR was observed in IECs from murine models and patients with IBDs. The authors' results indicate that PKR might link mitochondrial stress to intestinal inflammation.